THE ROLE OF ELECTRONIC NURSING DOCUMENTATION IN ENHANCING PATIENT CARE QUALITY: A SYSTEMATIC LITERATURE REVIEW - Siska Mayang Sari,; Faridah Mohd Said, (International Journal of Social Science, 2025)
Electronic nursing documentation (END) has become an essential component of modern nursing practice. The use of END is expected to improve the quality of patient care through more accurate and efficient record keeping. This article aims to evaluate the effectiveness of electronic nursing documentation in improving the quality of patient care. This systematic review study was conducted in June-July 2024 by searching the literature on electronic databases such as ProQuest, Science Direct, PubMed, and Google Scholar for articles published between 2019 and 2024. The keywords used included “electronic nursing documentation”, or “computerized nursing documentation” and “quality of care” and “nurse” “hospital”. Two reviewers independently screened the articles, extracted data, and assessed the quality of the included studies using the Systematic Reviews and Meta-Analyses (PRISMA). There were 9 articles met the inclusion criteria and were analysed further. The inclusion criteria were RCT and non RCT, cross sectional and observational study, and hospital setting, while the exclusion criteria were qualitative study and literature or systematic review. The analysis showed that the use of END significantly improved the quality of nursing care, enhanced communication and collaboration among healthcare providers, leading to improved patient outcomes. Besides, END improved documentation accuracy, time efficiency, operational efficiency, error reduction and patient safety. However, some challenges such as monitoring and evaluation from nurse managers regarding the accuracy and quality of documentation and the need for computer skills training are also needed. It Concluded the electronic nursing documentation has great potential to improve the quality of patient care in hospitals